2020
DOI: 10.1039/c9ce01587f
|View full text |Cite
|
Sign up to set email alerts
|

In situflow cell platform for examining calcium oxalate and calcium phosphate crystallization on films of basement membrane extract in the presence of urinary ‘inhibitors’

Abstract: The development of a flow-cell platform is reported that utilizes basement membrane extract as a biologically relevant crystallization substrate to study the effect of urinary inhibitors on the in situ formation of calcium oxalate/phosphate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 44 publications
3
16
0
Order By: Relevance
“…These microscopy-to-omics results pave the way for future experimentation, in which these hypotheses can be systematically tested using highly-controlled microfluidic devices (4,47). For instance, microfluidic testbeds can be used to quantitatively track the intermediate steps of kidney stone formation in real time under high-resolution microscopy, as in a recently published reports (2,3,47). This would allow specific mechanisms and processes controlling kidney stone growth and dissolution to be tested in the context of microbiome community, phylogenetic diversity, functional activity, and biochemistry.…”
Section: Discussionmentioning
confidence: 92%
“…These microscopy-to-omics results pave the way for future experimentation, in which these hypotheses can be systematically tested using highly-controlled microfluidic devices (4,47). For instance, microfluidic testbeds can be used to quantitatively track the intermediate steps of kidney stone formation in real time under high-resolution microscopy, as in a recently published reports (2,3,47). This would allow specific mechanisms and processes controlling kidney stone growth and dissolution to be tested in the context of microbiome community, phylogenetic diversity, functional activity, and biochemistry.…”
Section: Discussionmentioning
confidence: 92%
“…The polymer used in the PILP process, referred to as the process directing agent, was usually polyaspartate but similar anionic polyelectrolytes were also used [242,243]. Model systems were devised for biomimetic mineralization of collagen sponges [241,244,245] and models of bone [42,241,242,246], tendon [247], dentin [248] and soft tissues [249][250][251][252].…”
Section: Mineralization In the Extracellular Matrix Of Collagenous Hard Tissuesmentioning
confidence: 99%
“…Biomimetic studies of collagen mineralization were also been made with OPN [41,159,[250][251][252][253][254] and interpreted as due to the PILP mechanism. A comparative study showed that collagen mineralization using solutions containing OPN was more homogeneous, rapid and reproducible than with polyaspartate [159].…”
Section: Mineralization In the Extracellular Matrix Of Collagenous Hard Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Consequently, it appears clear that microfluidics by partially recreating the renal environment and the conditions promoting KS formation can contribute to the understanding of the underlying mechanisms. 22,23,24 Green tea (GT) is one of the most common beverages consumed around the world and has been reported to have potential anti-oxidative effects as well as preventive effects on diseases such as atherosclerosis or Parkinson's disease thanks to its rich content in polyphenols. 19,25,26 Recently, on the basis of clinical observations, the consumption of GT was considered for the treatment of KS, which led to a patent application for the use of its active ingredient, catechins (polyphenolic compounds from GT).…”
Section: Introductionmentioning
confidence: 99%